2015
DOI: 10.1186/s12893-015-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of postoperative pancreatic fistula after pancreatico-duodenectomy: an audit of 532 consecutive cases

Abstract: BackgroundPancreatic fistula (PF) remains the most challenging complication after pancreaticoduodenectomy (PD). The purpose of this study was to identify the risk factors of PF and delineate its impact on patient outcomes.MethodsWe retrospectively reviewed clinical data of 532 patients who underwent PD and divided them into PF group and no PF group. Risk factors and outcomes of PF following PD were examined.ResultsPF was found in 65 (12.2%) cases, of whom 11 were classified into ISGPF grade A, 42 grade B, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 30 publications
2
56
1
Order By: Relevance
“…Polanco et al . and Fu and colleagues both found that higher EBL and smaller pancreatic duct diameter were associated with a higher POPF rate, based on robotic and open pancreaticoduodenectomies. In addition, male sex and operating time over 180 min were independent determinants of grade B/C POPF.…”
Section: Discussionmentioning
confidence: 97%
“…Polanco et al . and Fu and colleagues both found that higher EBL and smaller pancreatic duct diameter were associated with a higher POPF rate, based on robotic and open pancreaticoduodenectomies. In addition, male sex and operating time over 180 min were independent determinants of grade B/C POPF.…”
Section: Discussionmentioning
confidence: 97%
“…Despite developments in anesthesia and surgery, the mortality of patients undergoing pancreaticoduodenectomy is about 5 %, owing to life-threatening complications mainly caused by pancreatic fistulas. [28][29][30][31] Supportive tools are necessary, especially for IPMN patients who are at poor risk for surgery, including those with chronic heart failure, chronic kidney disease, and severe liver cirrhosis. The current study demonstrated that NLR is significantly higher in patients with a malignant component than in patients with IPMA.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of patients undergoing PD are due to benign reasons, for example, intraductal papillary mucinous neoplasm. Anastomotic leakage and the subsequent pancreatic fistula are the most common surgical complications after a PD (3). Known risk factors of leakage have previously been identified including the diameter of the pancreatic duct, a soft pancreas texture, ischemia, perioperative bleeding, and body mass index (BMI) (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic leakage and the subsequent pancreatic fistula are the most common surgical complications after a PD (3). Known risk factors of leakage have previously been identified including the diameter of the pancreatic duct, a soft pancreas texture, ischemia, perioperative bleeding, and body mass index (BMI) (3,4). In addition, a prospectively validated clinical score that accurately predicts pancreatic fistulas after PD has been published (5).…”
Section: Introductionmentioning
confidence: 99%